2011
DOI: 10.1002/dta.225
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and biological investigation of the extracts of Nigella sativa L. seed waste

Abstract: Different extracts of Nigella sativa L. seed waste; aqueous (AE) 200 mg/kg, ethanol 70% (EE) 250 mg/kg and hexane (HE) 10 mg/kg, were evaluated for their hepatoprotective activities. They were administered orally, once daily, for 5 consecutive days. On day 5, liver injury was induced in animals by a single i.p. injection of carbon tetrachloride (10 mg/kg b. w. of 0.25% (v/v). Hepatoxicity produced, was evaluated by both biochemical and histopathological investigations. The aqueous extract attenuated the CCl(4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…injection of normal saline (2.5 mL/kg) on day 3. Animals in Group 2 (NSEE group) were given, orally by gavage, NSEE at 250 mg/kg (in normal saline of a total volume of 0.5 mL) daily for 5 successive days (33). Rats of Group 3 (DENA group) were given, for 5 successive days, the same dose of normal saline and a single dose of DENA (Sigma Chemical Company, St Louis, MO, USA) at 200 mg/2.5 mL per kilogram of body weight in saline, i.p.…”
Section: Experimental Designmentioning
confidence: 99%
“…injection of normal saline (2.5 mL/kg) on day 3. Animals in Group 2 (NSEE group) were given, orally by gavage, NSEE at 250 mg/kg (in normal saline of a total volume of 0.5 mL) daily for 5 successive days (33). Rats of Group 3 (DENA group) were given, for 5 successive days, the same dose of normal saline and a single dose of DENA (Sigma Chemical Company, St Louis, MO, USA) at 200 mg/2.5 mL per kilogram of body weight in saline, i.p.…”
Section: Experimental Designmentioning
confidence: 99%
“…Nigella sativa has the main active ingredient, thymoquinone has the ability to inhibit proinflammatory cytokines such as TNFα, interleukin-1, interleukin-6, NF-kβ [17][18][19]. Thymoquinone works as an inflammatory inhibitor that works through the pathway as an anti-inflammatory and proapoptotic.…”
Section: Positive Effects Of Black Cumin Ethanol Extract (Nigella Satmentioning
confidence: 99%
“…The results of chemical analysis of black cumin oil showed that the fixed oil content of line oleic acid, oleic acid, eicosanoat acid, palmitoleic acid, palmitic acid, stearic acid, myristic acid, sterols, and volatile oil showed the main active ingredient, thymoquinone (2-isopropyl-5-methylbenzoquinone) proved to have anti-inflammatory activity [16]. The main components of black cumin seeds, thymoquinone, have the ability to inhibit pro inflammatory cytokines such as TNF-α, interleukin-1, interleukin-6, NF-kB (nuclear factorkappa B) [17][18][19]. Thymoquinone works as an inflammatory inhibitor that works through the pathway as an antiinflammatory.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Some snow lotus healthcare products are even adulterated with other herbs, causing an inevitable concern to public health. [14][15][16] The more we looked into the three medicinal sources, the more we were convinced of the need for an in-depth investigation of the chemical constituents of such raw herbal products as the basis for extending their medical applications [17][18][19] as well as preventing falsification of the products on the market. [8][9][10] Some studies have authenticated different botanical origins of snow lotus medicines by observing macroscopic and microscopic features; [7,11,12] others have preliminarily analyzed chemical components and compared their pharmacological effects.…”
Section: Introductionmentioning
confidence: 99%
“…[5,13] We have also reviewed the literature on the three representative snow lotus herbs with regard to their botany, phytochemistry, and pharmacology, aiming to distinguish the three species from a comprehensive perspective. [14][15][16] The more we looked into the three medicinal sources, the more we were convinced of the need for an in-depth investigation of the chemical constituents of such raw herbal products as the basis for extending their medical applications [17][18][19] as well as preventing falsification of the products on the market. [20] This paper is our attempt to meet this need.…”
Section: Introductionmentioning
confidence: 99%